Amitraz intoxication in two cattle - Kizil, O.; Balikci, E.; Dabak, M.; Ozdemir, H. (Ecole Nationale Veterinaire Toulouse, 2008)
This paper presents the first clinical and biochemical findings and therapeutic management of amitraz intoxication in cattle. One Simmental cow aged 7 year old and one Simmental heifer aged 1 year old from a farm were referred to our clinic due to accidental intramuscular amitraz injection (respectively 19 and 10 ml of a 12.5% emulsifable concentrate aqueous solution). Clinical examination of the cattle revealed anorexia, depression, decreased ruminal concentration, scleral congestion, mild bloat and loss of pupillary reflex. The cattle were treated intravenously with yohimbine hydrochloride (0.1 mg/ka BW) improved clinically 24 hours after treatment.
Keywords: amitrazse; cattle; toxicity; yohimbine